Bibiliometric Mapping of Local Communities’ Environmental Conservation Behaviour - Supina, Supina; Iskandar, Hari (E-Journal of Tourism; Volume 10 Number 2 (September 2023)DO - 10.24922/eot.v10i2.100600, 2023)
Before new trends emerge after the COVID pandemic is over, this paper aims to examine the development of recent research trends in the theories and methods applied to studies of local communities' behaviours towards environmental protection in the years 2018–2021. This paper presents a review of more than one thousand local communities' environmental conservation behaviours that was published between 2018 and 2021. The purpose of this research is to achieve its objective. Following that, content analysis was performed on the articles that were pertinent. In order to clarify, categorise, and interpret the current research on rural tourism definitions and applications, a classification scheme and an extensive literature review have been presented in this article. Both of these elements are presented in this paper. A total of 38 academic papers from 25 different journals published between the years 2018 and 2021 are included in this review's classification scheme. These papers are organised according to their use of one of five primary keywords: local, community, environmental, conservation, or behaviour. The fact that the articles under consideration in this research were only found in the Scopus database represents a potential limitation of the bibliometric mapping. This research contributes to the existing body of knowledge by conducting a bibliometric review of studies that have already investigated locals' perspectives on tourism, and this review adds to the tourism literature by analysing the growing trend of looking at how different communities' actions affect environmental protection. Future research on these trends can be guided by identifying where the gaps in knowledge currently exist.